2001
DOI: 10.1152/jn.2001.85.6.2477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Expectation of Different Rewards on Behavior-Related Neuronal Activity in the Striatum

Abstract: This study investigated how different expected rewards influence behavior-related neuronal activity in the anterior striatum. In a spatial delayed-response task, monkeys reached for a left or right target and obtained a small quantity of one of two juices (apple, grenadine, orange, lemon, black currant, or raspberry). In each trial, an initial instruction picture indicated the behavioral target and predicted the reward. Nonmovement trials served as controls for movement relationships. Consistent preferences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
203
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(235 citation statements)
references
References 44 publications
24
203
3
4
Order By: Relevance
“…Similarly, dopamine measurements in the NAc using fast-scan cyclic voltammetry have shown a greater amount of dopamine delivered following an S+ compared to an S− cue after Pavlovian conditioning (Day et al, 2007;Stuber et al, 2008). Finally, neuronal firing in the NAc has been shown to commence rapidly after cue onset and to be greater for S+ than S− cues (Hassani et al, 2001;Nicola et al, 2004). Thus, release of dopamine in the NAc from VTA afferents and nucleus accumbens neuronal activity are both clearly implicated in encoding the predictive value of rewarding cues.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, dopamine measurements in the NAc using fast-scan cyclic voltammetry have shown a greater amount of dopamine delivered following an S+ compared to an S− cue after Pavlovian conditioning (Day et al, 2007;Stuber et al, 2008). Finally, neuronal firing in the NAc has been shown to commence rapidly after cue onset and to be greater for S+ than S− cues (Hassani et al, 2001;Nicola et al, 2004). Thus, release of dopamine in the NAc from VTA afferents and nucleus accumbens neuronal activity are both clearly implicated in encoding the predictive value of rewarding cues.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 92%
“…Other studies of electrophysiology and dopamine release in rats have also shown that both neuronal firing or dopamine release tend to signal the "better" of two reward options rather than their absolute value (Day et al, 2010;Roesch et al, 2007). Studies in monkeys have also tried to address whether striatal activations incorporate details of upcoming rewards and have demonstrated differences in activation patterns induced by two different types of juices (Hassani et al, 2001) as well as rewards of different magnitudes (Cromwell and Schultz, 2003). Finally, human neuroimaging studies have shown a specific relationship between BOLD signal increase in the NAc and magnitude of reward (Cooper and Knutson, 2008;Knutson and Cooper, 2005;Yacubian et al, 2006) and dichotomous activation for the cue predicting the greatest available reward value has also been observed (Ballard and Knutson, 2009).…”
Section: Nucleus Accumbens Activation and Reward Magnitude Codingmentioning
confidence: 99%
“…Tonic delay period activity of several hundred milliseconds duration that anticipates stimuli, rewards or the animal's own actions was termed 'anticipatory', 'preparatory', or 'predictive' and has been reported in the striatum, supplementary motor area, prefrontal cortex, orbitofrontal cortex, premotor cortex, and primary motor cortex (Schultz, 2000;Suri & Schultz, 2001). The characteristics of rewardanticipatory neural activity in frontal cortices resemble those in the striatum (Hassani, Cromwell, & Schultz, 2001).…”
Section: Prediction Activity In Striatum and Cortexmentioning
confidence: 93%
“…Second, since Parkinsonian patients seem to be impaired in planning tasks, dopamine may be involved in planning (Lange et al, 1992;Wallesch et al, 1990). Third, reward-specific and event-specific anticipatory neural activities in cortex and striatum represent the outcome of their actions already at the time of the behavior towards the outcome, which is typical for internal model approaches and not required for the standard TD model (Hassani et al, 2001;Schultz, 2000). For these reasons, I propose to model dopamine neuron activity and anticipatory neural activity in striatum and cortex with an internal model approach (Suri, 2001) and to use the dopamine-like signal of this internal model to select the correct actions in the Actor network ).…”
Section: Internal Model Approachesmentioning
confidence: 99%
“…In addition to their involvement in motor functions, the basal ganglia nuclei are involved in coding reward prediction and reward delivery (Arkadir et al, 2004;Darbaky et al, 2005;Hassani et al, 2001;Hollerman et al, 1998) and in the reinforcing properties of alcohol (Bassareo et al, 2003;Melendez et al, 2004). Within the cortico-basal ganglia-thalamocortical limbic loop, the subthalamic nucleus (STN) is a key structure that may modulate the basal ganglia outflow (Turner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%